2007
DOI: 10.1080/14756360701485901
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and PC3 androgen-independent prostate cells antiproliferative effect of fagaronine derivatives

Abstract: Fagaronine derivatives syntheses were optimized and their effect on PC3 androgen-independent prostate cell line was evaluated. An assessment of the lipophilicity of the benzo[c ]phenanthridine derivatives was achieved at pH 7.4 and et 6.7 by determining log D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…26) However, when the same method was used for preparation of 4-1 from 3-1, the reaction only gave less than 10% yield, and most of 3-1 was recovered. Next, the iodine oxidation 34) was also tested but without encouraging result.…”
Section: Resultsmentioning
confidence: 99%
“…26) However, when the same method was used for preparation of 4-1 from 3-1, the reaction only gave less than 10% yield, and most of 3-1 was recovered. Next, the iodine oxidation 34) was also tested but without encouraging result.…”
Section: Resultsmentioning
confidence: 99%
“…Due to its high toxicity and insolubility in biological fluids, this compound is not currently used in vivo [16]. Derivatives of fagaronine have been thus synthesized in order to improve their potency as anti-leukemic agents while reducing their toxicity [20,32].…”
Section: Discussionmentioning
confidence: 99%
“…high toxicity and insolubility in biological fluids render fagaronine unusable in vivo [31]. In order to improve the anti-leukemic potency while reducing the toxicity of benzo[c]-phenanthridines, derivatives of fagaronine like ethoxfagaronine (etxfag) have been synthesized [20,32]. Etxfag exhibits higher solubility in aqueous solvents and we recently reported that it reduced murine leukemic L1210 cell invasiveness [22].…”
Section: Discussionmentioning
confidence: 99%
“…Adherent cells were incubated with 25 M LY294002 or 25 M LY303511 for 30 min before lysed. Anti-p85 immunoprecipitates were subjected to PI 3-kinase activity determined by PI phosphorylation in the presence of [␥-32 P] ATP. Phosphorylated PI (PIP) was separated by TLC and analysed by autoradiography.…”
mentioning
confidence: 99%